A chromatic presence: Barbara Hammer and "What You Are Not Supposed to Look At". Issue 3 (2nd September 2019) - Catbagan, Maureen; Musser, Amber Jamilla
Abstract : Since the 1970s, Barbara Hammer has been known for her photographs and experimental films chronicling and exploring lesbian experience. Since her 2006 diagnosis of ovarian cancer, she has ventured into an unflinching depiction of her own illness, aging, and dying. In "What You Are Not Supposed to Look At, " a 2014 collage series collaboration with Ingrid Christie, Hammer and Christie illuminate new modes of thinking about life, illness, and what we are describing the prismatic gaze: a mode of looking that subverts objectification and objectivity by positing sensuality, relationality, and spectacularity.